2015
DOI: 10.1111/chd.12279
|View full text |Cite
|
Sign up to set email alerts
|

Modern Incidence of Complete Heart Block in Patients with L-looped Ventricles: Does Univentricular Status Matter?

Abstract: All patients with L-transposition of the great arteries have similar risk of spontaneous complete heart block and should be routinely screened for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…As reported previously, depending on the alterations in the conduction system, there is an equal risk for development of spontaneous complete AVB in both single‐ and two‐ventricle patients . In the present study, none of the single‐ventricle patients developed perioperative complete AVB.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As reported previously, depending on the alterations in the conduction system, there is an equal risk for development of spontaneous complete AVB in both single‐ and two‐ventricle patients . In the present study, none of the single‐ventricle patients developed perioperative complete AVB.…”
Section: Discussionsupporting
confidence: 77%
“…As reported previously, depending on the alterations in the conduction system, there is an equal risk for development of spontaneous complete AVB in both single-and two-ventricle patients. 17 In the pres- ccTGA. 19 They concluded that were only a few documented cases of ventricular tachycardia in patients with ccTGA.…”
mentioning
confidence: 99%
“…The natural incidence of complete heart block in ccTGA is approximately 1% to 2% per 100 patient-years. 16 The management of pacing is an integral part of management of ccTGA. Summarized details of pacing systems are provided in Table E2.…”
Section: Timementioning
confidence: 99%
“…During the Fontan operation, unipolar epicardial leads were placed on the right atrial appendage and right ventricle as a preemptive measure, given the high risk of AV nodal block in patients with L-transposition. 3 This patient did well clinically, and was without need for cardiac pacing until age 23 years, when progressive AV nodal block was discovered. Given the complex anatomy of this patient's initial CHD and corrective surgeries, the previously abandoned epicardial leads were visualized with fluoroscopy, dissected out from the upper abdominal wall, uncapped, and attached to a new abdominal generator, leading to successful restoration of AV synchrony ( Table 1 ).…”
Section: Case Reportsmentioning
confidence: 80%